Dye-sensitized solar cells : emerging trends and advanced applications - Pandey, Adarsh Kumar (Academic Press, an imprint of Elsevier, 2022)
"The technology of dye-sensitized solar cell[s] is growing rapidly due to its cost-effective and easy fabrication, environmental friendliness, and ability to absorb new scientific approaches. Dye-Sensitized Solar Cells: Emerging Trends and Advanced Applications is highly focused on addressing all aspects of dye-sensitized solar cell technology. In this book the authors present systematic analysis and working principles along with detailed studies of individual components, manufacturing methods, software-assisted design, the technology market, and commercialization potential. The book provides a comprehensive study on dye-sensitized solar cells and covers basic working principles to advanced approaches in improving efficiency as well as thermodynamic and kinetic studies, making this book useful for developing or advanced stage researchers and engineers looking to get a grip on DSSC technology"--Print version, page 4 of cover.